Beyond the Context: Exploring the Use of Deixis in Taylor Swift’s Folklore Album - Siagian, Tesalonika Lamriama; Ma'shumah, Nadia Khumairo (Deskripsi Bahasa, 2025)
While deixis has long been recognized as a key feature of everyday communication for the way it connects language to its immediate context, there is still little research that looks at how it works in contemporary music. This study was designed to investigate the representation of deixis in Taylor Swift’s Folklore album, drawing on Yule's (1966) categorizations. A total of 1,160 occurrences of deixis were systematically collected and analyzed through a mixed-methods approach. The analysis demonstrated that deixis in Folklore serves as a narrative device that situates stories and emotions within particular times, spaces, and also social relations. Among the three types, personal deixis is the most prominent type, demonstrating the album’s clear orientation toward social interaction. Temporal deixis appears at a moderate level, pointing to an interest in time-related contexts, while spatial deixis is used least often, revealing a smaller emphasis on locational aspects. These distributions further highlight how personal and discourse deixis operate as the central mechanisms for creating coherence and sustaining the contextual grounding of the album’s narratives.